Mono-Heteromeric Configurations of Gap Junction Channels Formed by Connexin43 and Connexin45 Reduce Unitary Conductance and Determine both Voltage Gating and Metabolic Flux Asymmetry - Zhong, Guoqiang; Akoum, Nazem; Appadurai, Daniel A.; Hayrapetyan, Volodya; Ahmed, Osman; Martinez, Agustin D.; Beyer, Eric C.; Moreno, Alonso P. (Frontiers in Physiology, 2017)
In cardiac tissues, the expression of multiple connexins (Cx40, Cx43, Cx45 and Cx30.2) is a requirement for proper development and function. Gap junctions formed by these connexins have distinct permeability and gating mechanisms. Since a single cell can express more than one connexin isoform, the formation of hetero-multimeric gap junction channels provides a tissue with an enormous repertoire of combinations to modulate intercellular communication. To study further the perm-selectivity and gating properties of channels containing Cx43 and Cx45, we studied two monoheteromeric combinations in which a HeLa cell co-transfected with Cx43 and Cx45 was paired with a cell expressing only one of these connexins. Macroscopic measurements of total conductance between cell pairs indicated a drastic reduction in total conductance for mono-heteromeric channels. In terms of Vj dependent gating, Cx43 homomeric connexons facing heteromeric connexons only responded weakly to voltage negativity. Cx45 homomeric connexons exhibited no change in Vj gating when facing heteromeric connexons. The distributions of unitary conductances (j) for both mono-heteromeric channels were smaller than predicted, and both showed low permeability to the fluorescent dyes Lucifer yellow and Rhodamine123. For both mono-heteromeric channels, we observed flux asymmetry regardless of dye charge: flux was higher in the direction of the heteromeric connexon for MhetCx45 and in the direction of the homomeric Cx43 connexon for MhetCx43. Thus, our data suggest that co-expression of Cx45 and Cx43 induces the formation of heteromeric connexons with greatly reduced permeability and unitary conductance. Furthermore, it increases the asymmetry for voltage gating for opposing connexons, and it favors asymmetric flux of molecules across the junction that depends primarily on the size (not the charge) of the crossing molecules.